Tribological performance of ionic liquid-lubricated carbon brush/collector ring current-carrying friction system - Yang Fu (Biosurface and Biotribology, 2020)
The lubricity and anti-wear ability of ionic liquids (ILs) were studied by a current-carrying friction test on IL-lubricated carbon brushes. The results indicated that the conductivity and wear resistance of different ILs are different, and may vary for different carbon brushes. The E468e carbon brush was found to be more sensitive to IL lubrication than D172 carbon brush. Importantly, an analysis of the wear surfaces of the D172 and E468e carbon brushes revealed that, due to the different materials of the two carbon brushes and the composition of the IL, the lubrication effect on the carbon brushes was different. The viscosity of the IL will affect its wettability on the carbon brush surface. The better the wettability, the easier the movement of ions on the surface, which makes it easier to form a conductive physical adsorption film. Therefore, in practice, a better IL must be selected by considering the wettability of IL and carbon brushes.